The Inka Ceramic Record in the Puna of Jujuy (Argentina): an Approach Based on Museum Collections - Perez Pieroni, María Josefina (2021)
In order to provide greater insights into the understanding of state influence on ceramic production in the Puna of Jujuy (Argentina), we analyze/study a set of 43 vessels considered of Inka influence and chronology according to their morphologies and design motifs. These vessels come from different archaeological sites in the region, mainly from funerary contexts, and are deposited in museum collections. Different macroscopic attributes were registered, in relation to the operative production chain. In addition, a morphological classification is proposed based on reports/findings from other authors. The results allow us to suggest a production of Inka-influenced forms/designs within local technological traditions of late pre-Hispanic times, particularly those linked to the Yavi-chicha ceramic style. The elements incorporated mainly comprise morphologies/forms found across the empire and that probably served as indexes of the imperial presence in the different negotiation relationships developed by the Inkas.